Penerapan Azas Itikad Baik dalam Transaksi Jual Beli Online demi Mewujudkan Kepastian Hukum - Dollar Dollar; Khairul Riza (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2022)
Purpose: To determine the legal regulation of the principle of good faith in the implementation of online buying and selling transaction agreements, and to find out the application of the principle of good faith in online buying and selling transactions in order to realize legal certainty. Method: used is normative juridical research through literature study with an approach to legislation and books. Result: The research is that the legal regulation of the principle of good faith in the implementation of online buying and selling transactions is regulated in Article 530 of the Civil Code which states that good faith in a subjective sense is an inner attitude or a state of mind, good faith in a subjective sense is called honesty. In addition, it is regulated in Article 1338 of the Civil Code paragraph (3) which states that an agreement must be carried out in good faith, good faith in an objective sense is called propriety. The application of the principle of good faith in online buying and selling transactions through the marketplace to provide legal certainty to the public, especially consumers, is the same as the application of the principle of good faith in buying and selling agreements in ordinary interactions. It's just that the application of sanctions or the implementation of a lawsuit against the party who is in default in the agreement is difficult to implement because the parties do not know each other's identity or whereabouts. Therefore, the success of implementing an online sale and purchase agreement can only be achieved in good faith from the parties.